Agile scores in MASLD and ALD: External validation and their utility in clinical algorithms - Papatheodoridi, Margarita; De Ledinghen, Victor; Lupsor-Platon, Monica; Bronte, Fabrizio; Boursier, Jerome; Elshaarawy, Omar; Marra, Fabio; Thiele, Maja; Markakis, Georgios; Payance, Audrey; Brodkin, Edgar; Castera, Laurent; et al. (Journal of hepatology, 2024)
Background & Aims - Agile scores, including liver stiffness measurements (LSM) and routine clinical/laboratory biomarkers, have been developed for advanced fibrosis (F≥3) and cirrhosis (F4), respectively, in patients with metabolic dysfunction-associated steatotic liver disease (MASLD). We independently validated the diagnostic accuracy of these scores in MASLD, alcohol-related liver disease (ALD) and chronic hepatitis B or C (CHB/C) and assessed them in clinical algorithms with FIB-4 and LSM. - Methods - We included 4,243 patients (MASLD: 912, ALD: 386, CHB: 597, CHC: 2,348) with LSM, liver biopsy and laboratory tests within 6 months. FIB-4, Agile 3+ and Agile 4 scores were calculated. - Results - For F≥3, the diagnostic accuracy of Agile 3+ and LSM were similar in MASLD (AUC: 0.86 vs. 0.86, p = 0.831) and ALD (0.92 vs. 0.94, p = 0.123). For cirrhosis, Agile 4 was similar to LSM in MASLD (0.89 vs. 0.90, p = 0.412) and ALD (0.94 vs. 0.95, p = 0.513). Agile 3+/4 performed worse than LSM in CHB/C. Using predefined dual thresholds of 90% sensitivity/specificity, correct classification rates in MASLD were 66% vs. 61% using Agile 3+ vs. LS dual cut-offs and 71% vs. 67% in ALD, respectively. When using Agile 3+ or LSM as a second step after FIB-4 >1.3, correct classification rates were higher with Agile 3+ than LSM, both for MASLD (75% vs. 71%) and ALD (76% vs. 72%), with fewer indeterminate results. Positive agreement of LSM and Agile 3+/4 significantly increased the specificity of a diagnosis of advanced fibrosis/cirrhosis. - Conclusion - Agile 3+ and Agile 4 have equal diagnostic accuracy with LSM in both MASLD and ALD but result in fewer indeterminate results. Sequential use of FIB-4 and Agile 3+/4 or concurrent Agile 3+/4 and LSM can be used to further optimize F≥3 diagnosis. - Impact and implications - As of today, it is accepted that there will be no single non-invasive test or an isolated cut-off for identifying patients with advanced chronic liver disease. Here, we confirmed that Agile 3+ and Agile 4 scores are useful alternatives to simple liver stiffness measurement in diagnosing advanced fibrosis/cirrhosis in steatotic liver disease, but they do not perform as well in chronic viral hepatitis. Agile scores can help optimize the diagnosis of advanced fibrosis/cirrhosis in a dual cut-off strategy by reducing the number of indeterminate results either alone or in a sequential strategy after FIB-4. The combination of Agile scores and liver stiffness measurement can further increase our confidence in a positive diagnosis of advanced fibrosis/cirrhosis. These novel combination strategies can be useful tools to predict the likelihood of advanced stages of liver disease with the highest possible accuracy in a secondary/tertiary healthcare setting.